Personal insult disrupts regulatory brain networks in violent offenders. (19th September 2022) - Hofhansel, Lena; Weidler, Carmen; Clemens, Benjamin; Habel, Ute; Votinov, Mikhail
Abstract: The failure to adequately regulate negative emotions represents a prominent characteristic of violent offenders. In this functional magnetic resonance imaging study, we used technical, nonsocial frustration to elicit anger in violent offenders ( n = 19) and then increased the provocation by adding personal insults (social provocation). The aim was to investigate neural connectivity patterns involved in anger processing, to detect the effect of increasing provocation by personal insult, and to compare anger-related connectivity patterns between offenders and noncriminal controls ( n = 12). During technical frustration, the offenders showed increased neural connectivity between the amygdala and prefrontal cortex compared to the controls. Conversely, personal insults, and thus increased levels of provocation, resulted in a significant reduction of neural connectivity between regions involved in cognitive control in the offenders but not controls. We conclude that, when (nonsocially) frustrated, offenders were able to employ regulatory brain networks by displaying stronger connectivity between regulatory prefrontal and limbic regions than noncriminal controls. In addition, offenders seemed particularly sensitive to personal insults, which led to increased implicit aggression (by means of motoric responses) and reduced connectivity in networks involved in cognitive control (including dorsomedial prefrontal cortex, precuneus, middle/superior temporal regions).